Martin Luther : the Christian between God and death - Marius, Richard (Belknap Press of Harvard University Press, 1999)
Marius follows Luther from his birth in Saxony in 1483, during the reign of Frederick III, through his schooling in Erfurt, his flight to an Augustinian monastery and ordination to the outbreak of his revolt against Rome in 1517, the Wittenberg years, his progress to Worms, his exile in the Wartburg, and his triumphant return to Wittenberg. Throughout, Marius pauses to acquaint us with pertinent issues: the question of authority in the church, the theology of penance, the timing of Luther's "Reformation break-through," the German peasantry in 1525, Muntzer's revolutionaries, the whys and hows of Luther's attack on Erasmus. In this personal, occasionally irreverent, always humane reconstruction, Luther emerges as a skeptic who hated skepticism and whose titanic wrestling with the dilemma of the desire for faith and the omnipresence of doubt and fear became an augury for the development of the modern religious consciousness of the West. In all of this, he also represents tragedy, with the goodness of his works overmatched by their calamitous effects on religion and society.